Analysis of meteorological drought in Tihama Plain, Yemen using Standardized Precipitation Index (SPI) - Dhaif Allah Ali Ahmed, Md Hashim Noorazuan (Universiti Pendidikan Sultan Idris, 2016)
Analysis of meteorological drought in Tihama Plain, Yemen using Standardized Precipitation Index (SPI) by Dhaif Allah Ali Ahmed, Md Hashim Noorazuan,